The legal system of land conservation in Algerian legislation - Noureddine Hairech; Souad Yahiaoui (Social Empowerment Journal, 2019)
The building is considered one of the most important things belonging to people, and this is one of the most important things for the rich, that you find people who try and do as much as possible to preserve and protect it in every way possible so that it is not exposed to looting, appropriation, sabotage or encroachment by others by selling. Consequently, the legislator has set up an administrative body whose task is to protect the immovable property under its jurisdiction and to record and month all acts against it or which are dealt with therein, in addition to the task of informing other transactors in real estate of everything that is happening on it. This system is the Land Conservation, which is the only authority authorized to declare all property within its jurisdiction.